Hasil Belajar Matematikamelalui Model Pembelajaran Dan Disiplin Belajar - Virgana Virgana (Faktor Jurnal Ilmiah Kependidikan, 2017)
Abstract. This experiment research is aimed that the students’ result of study in Mathematics is caused by cooperative learning model of type Student Team Achievement Division and discipline of study. Research has been implemented using experimental variables after all put into 2 x 2 factorial design. In this research, the students have been chosen as a unit of analysis 60 samples. Research instruments have been tested with reliability coefficients = 0.887, and test the results of learning math multiple choice  that have been tested with reliability coefficients validity = 0.884. The analysis of the data using Analysis of variance (ANOVA) two directions. The result of analysis finds out that: 1) the students ' result of study in Mathematics is the caused by cooperative learning model of type Student Team Achievement Division  against the results of learning math, 2) influence of learning discipline against the results of learning math students, and 3) the influence of interaction of the learning model cooperative type of Student Team Achievement Division and learn discipline against the results of the study of mathematics students.  Keywords: experiment, cooperative learning, discipline of study, and the results of the study